GIS-MODELING OF LAKE ONEGO SHORELINE IN THE HOLOCENE AND LATE PLEISTOCENE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The application of GIS software for reconstruction of Lake Onego shoreline in the Holocene and the Late Pleistocene presented. Reconstruction was originated from the ideas of the Lake Onego depression deglaciation model proposed by I. Demidov [1] and the data of E. Deviatova [2] concerning Lake Onego depression isostatic uplift in the Holocene. ArcGIS software was used to perform GIS-modelling which was based on the original digital elevation model of the lakebed and its watershed. Twelve digital paleogeographic maps were developed as a result. Paleogeographic maps were verified by hand-drawn images of I. Demidov and E. Deviatova and by matching the lake shoreline and the position of archeological sites. Maps are available on-line in the electronic form [3]. The surface area of the Lake was determined at different stages of its development. The quantitative data obtained in this study is valuable for estimation of the lake volumes and the rates of discharge in the past.